Rare causes of respiratory insufficiency in newborns - Brucknerová, Jana; Babala, Jozef; Ujházy, Eduard; Mach, Mojmír; Juránek, Ivo; Brucknerová, Ingrid (Physiological research, 2020)
Congenital lung masses (CLM) the rare group of causes of acute respiratory insufficiency (RI) in newborns include congenital airway pulmonary malformation (CAPM), congenital overinflation, bronchopulmonary sequestration, and bronchial atresia. The presenting group consists of 13 newborns who were admitted to the Neonatal Department of Intensive Medicine (NDIM) during January 1st 2015-December 31st 2019 (8 males, 5 females, 2 premature/11 term newborns, spontaneous delivery: 2, caesarean section: 11) with positive prenatal diagnosis of CAPM in all cases. In 2 cases prenatal intervention was performed (drainage of the amniotic fluid, attempt of thoracentesis). Signs of acute RI immediately after delivery were seen in 5 newborns. Postnatal echocardiographic investigation confirmed the presence of increased pulmonary pressure in 8 patients, no patient had congenital heart abnormality. A thorax x-ray was positive also in asymptomatic patients. Computed tomography in patients brought detailed information about the position, size and character of CAPM. Six patients underwent surgery. In 15.4 % right lungs were affected by cystic malformation and in 23 % left lungs were affected. A final diagnosis of CAPM was confirmed in 5 patients using histopathologic examination. Multidisciplinary cooperation during prenatal as well as postnatal period is necessary.
Keywords: plíce; Tomography, X-Ray Computed; pneumektomie; retrospektivní studie; cystická adenomatoidní malformace plic vrozená; Humans; respirační insuficience; Risk Factors; mužské pohlaví; Lung; Infant, Newborn; výsledek terapie; rizikové faktory; Cystic Adenomatoid Malformation of Lung, Congenital; Respiratory Insufficiency; Treatment Outcome; novorozenec; ženské pohlaví; lidé; Pneumonectomy; počítačová rentgenová tomografie; Male; Retrospective Studies; Female